Media Pembelajaran yang Memberdayakan: Studi Awal terhadap Ownership of Learning dan Literasi Digital Mahasiswa - Alfiatus Sa'diyah; Balqis; Herawati Susilo (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to analyze the needs for digital learning media in the Plant Physiology course as a foundation for developing an innovative learning model based on Problem-Based Learning (PBL) supported by a Deep Learning approach and the integration of Artificial Intelligence (AI). The research employed a quantitative descriptive method involving 42 students and 4 Biology Education lecturers. Data were collected through questionnaires, interviews, and document analysis, and analyzed descriptively. The findings indicate that the availability of teaching  materials  remains  limited  and  learning  media  are  still  predominantly conventional, mainly PowerPoint presentations and textbooks, while the utilization of interactive  digital  media  is  relatively  low. Students’ ownership of learning is categorized as good, with persistence as the most dominant aspect, whereas digital literacy is categorized as competent, with the ability to use AI technology identified as an aspect that requires further enhancement. In conclusion, the development of an AI-integrated flipbook e-module based on PBL is considered relevant to support Plant Physiology learning, as it has the potential to strengthen learning autonomy, enhance ownership of learning, and expand students’ digital literacy in an adaptive and personalized manner. Keywords: Artificial Intelligence, Deep Learning, Digital Literacy, E-Module Flipbook, Ownership of Learning, Plant Physiology, Problem-Based Learning.